Pin on Disc Tests of Closed Cell Aluminium Foams - Gábora, András; Kalácska, Gábor; Keresztes, Róbert; Beke, Sándor; Géresi, Zoltán Gergő (International Journal of Engineering and Management Sciences, 2020)
Metal foams have a lightweight cellular structure with excellent mechanical and physical properties and are at the forefront of materials development for the automotive and other industries. Although metal foams are popular, they are still not sufficiently characterized thanks to their extremely complex structure. The aim of the research is the tribological investigation of closed cell metal foams with different production technologies and different cell sizes. The paper introduces the closed cell aluminium foams produced by direct foaming and gas injection and those raw materials. The Pin on Disc instrument and the most important parameters of the experiments are also presented.